SOBRE RELIGIÃO, ESTADO LAICO E CIDADANIA LGBT+: A FRENTE PARLAMENTAR EVANGÉLICA E A DEFESA DA VERDADE SOBRE A FAMÍLIA - DIAS, Tainah Biela. (2017)
The purpose of this dissertation is to analyze the construction of a discourse of truth about the family by the evangelical parliamentarians who form the Evangelical Parliamentary Front (FPE). In order to achieve this objective, Law Projects (LP) and Legislative Decree Projects (LDP) have been proposed by FPE members that aimed at institutionalizing legally and politically the heterosexual and monogamous family as the only legitimate one, to the detriment of other arrangements, especially those formed by individuals that integrate the LGBT+ population. Speeches given by them have also been used and are available in the Diaries of the Chamber of Deputies. This research used a qualitative approach to reach the proposed objectives, through the explanation of the discourses of truth and later analysis with the necessary theoretical reference. We concluded that the defense of a truth about the family aims at perpetuating a traditional sexual morality based on the submission of the woman to the man and that is put in check by families formed by LGBT+ people, as they question the social roles attributed to men and Women in society. In addition, we came to the conclusion that this defense, made by political and religious agents, sets challenges to secularism, democracy and the consolidation of the citizenship of LGBT+ people.